INTERAKSI SOSIAL ASOSIATIF DALAM BENTUK KERJASAMA ANTAR SUKU DAYAK RIBUN DAN JAWA - Ria, Hildegardis; Aminuyati, Aminuyati; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe associative social interactions in the form ofcooperation between the Dayak Ribun and Javanese people at Kelompu Villageneighborhood one, Kembayan sub-district of Sanggau Regency. The focus of thisresearch was the discussion of harmony in cooperation, driving factors for thecommunity